Performativity and accountability in education: a look from the «neurological paradigm» of Byung Chul Han - Sergio Antonio Bravo Cuevas; Enric Prats Gil (Foro de educación, 2021)
The following article proposes a link between the reflection posed by Byung Chul Han and his psycho-political approach to the understanding of contemporary society – or burnout society – in relation to performative practices in the school setting that has described Stephen Ball’s theoretical contribution. A relationship is raised between the neurological paradigm, the power and control strategies of neoliberal society described by Han with the progressive transformation of practices in the school organization at the micro level, driven through accountability. In both cases, the improvement of the political technologies of the panoptic towards forms of control located internally of the subject and whose correlation is subjective is identified. Training for entrepreneurship, gamification of teaching and transformations in the teaching professional identity in a specific post-professional context that allow the school to identify the influence of the neurological paradigm on education. The conclusions raise the progressive articulation of the educational system to the requests and requirements of the neoliberal society, so that the school institution assumes as the proposal of sending in the performance society.